Complement component-7 is a long-term predictor of all-cause mortality in chest-pain patients with suspected acute coronary syndrome. (25th November 2020) - Aarsetoey, R; Ueland, T; Aukrust, P; Michelsen, A.E; Ponitz, V; Brugger-Andersen, T; Leon De La Fuente, R; Staines, H; Nilsen, D.W.T
Abstract: Introduction: The complement cascade is an important component of the innate immune system. Complement activation plays a major role in chronic inflammation and has been associated with atherosclerosis, atherosclerotic plaque destabilization and increased risk of cardiovascular events. Complement component 7 (C7) binds C5bC6 complex being part of the terminal complement complex (TCC/C5b-9). Purpose: To investigate the prognostic utility of complement C7 for long-term outcome in patients with suspected acute coronary syndrome (ACS). Methods: Complement C7 plasma-levels were measured by enzyme immunoassay in admission samples from 1823 patients included in a transatlantic prospective cohort study, which consecutively included hospital admitted chest-pain patients with clinically suspected ACS from South-Western Norway and Northern Argentina. Data were pooled for analysis. Univariable- and multivariable Cox proportional-hazards models were fitted for the analysis of all-cause mortality, cardiac death and sudden cardiac death (SCD) within 24 months, applying both quartiles (Q1–4) and loge-transformed continuous values of complement C7. Results: There were 253 (13.9%) deaths, of which 150 (8.2%) were categorized as cardiac death and 76 (4.2%) as SCD. Complement C7 levels were significantly higher in patients who died as compared to long-term survivors [176.9 (142.1–228.7) μg/mL versus 139.8 (110.6–179.7) μg/mL (median, 25 and 75% percentile), p<0.001], and were significantly associated with 24-month survival [log rank p<0.001 for all-cause mortality and cardiac death, log rank p=0.035 for SCD]. In univariable analysis, patients with complement C7-concentrations in the highest quartiles had significantly increased risk of all-cause mortality (Figure 1), cardiac death [Q4: Hazard Ratio (HR) 4.58 (95% confidence interval (CI): 2.65–7.92), p<0.001, Q3: HR 2.69 (95% CI: 1.51–4.80), p=0.001] and SCD [Q4: HR 2.83 (95% CI: 1.36–5.90), p=0.005, Q3: HR 2.33 (95% CI: 1.10–4.92), p=0.027] compared to patients in the lowest quartile (Q1). After adjusting for conventional clinical risk factors for coronary heart disease, complement C7-concentrations in Q4 [HR 2.09 (95% CI: 1.23–3.57), p=0.007] and Q3 [HR 2.21 (95% CI: 1.29–3.81), p=0.004] remained significantly associated with all-cause mortality, reproduced using loge-transformed continuous values. Conclusion: High levels of complement C7 were found to independently predict long-term all-cause mortality in chest-pain patients with clinically suspected ACS. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Western Norway Regional Health Authority